Balloon dilatation of a benign biliary stricture through a T-tube tract - Gupta, Pankaj; Kalra, Naveen; Kumar, Ajay; Kochhar, Rakesh; Gupta, Vikas; Khandelwal, Niranjan (Indian Journal of Radiology and Imaging, 2015)
Percutaneous cholangioplasty is a commonly performed procedure for both benign and malignant diseases. The most common route for accessing the biliary tree is transhepatic, following ultrasound or fluoroscopic-guided percutaneous puncture. There are situations when alternative routes can be utilized to access the common bile duct (CBD). We accessed the CBD via T-tube placed surgically in a 57-year-old man who had obstructive jaundice of obscure etiology which was likely inflammatory.
Keywords: Balloon dilatation; cholangioplasty; T-tube